BULB AND SEED YIELD POTENTIALS OF SUMMER ONION VARIETY DEVELOPED THROUGH INDUCED MUTATION - Azad, M. A. K.; Ali, M.; Yasmine, F.; Kamruzzaman, M. (Bangladesh Journal of Plant Breeding and Genetics, 2017)
With a view to improve bulb and seed yield potentials of summer onion, seeds of BARI Piaz-2 were irradiated with 75 Gy, 100 Gy and 125 Gy doses of gamma rays from a 60Co source in 2006.Fifty four days old seedlings were transplanted on 20 January 2007.Thirteen, 12 and 9 M1 plants, respectively, from 75 Gy, 100 Gy and 125 Gy dosesproduced fertile seeds which were kept separately dose wise. In M2 generation, seedlings of 13 progenies from 75 Gy, 10 from 100 Gy and 7 from 125 Gy were transplanted on 15 December 2008 in plant- progeny- rows and 11, 7 and 6, respectively, were selected based on higher percentage of seed producing plants compare to parent BARI Piaz-2.In M3and M4 generations, 13 progenies, 6 each from 75 Gy and 100 Gy and the other from 125 Gy were further selected based on higher seed yield than the parent. Additionally, in M3 generation, observation trial with the above 13 mutant lines for bulb yield potential in Kharif-I seasonin 2011 revealed the mutant lines BP2/75/5 and BP2/100/2 had significantly higher fresh and dry bulb yield than BARI Piaz-2 and that of BP2/75/2 had not differed significantly. Shelf life expressed here as rate of weight loss on storage for 2.0 months under ambient condition exhibited all the 13 mutants had longer shelf life than the parent and the check variety. The mutant BP2/100/2 had the longest shelf life followed by BP2/125/1 and BP2/100/12 and BP2/75/13. Preliminary yield trial for seed yield potential in M4 generation in winter season of 2011-2012 showed all the 13 mutant lines could produce seed from seed in the same season but the parent BARI Piaz-2 failed. In advance yield trial for bulb yield potential in Kharif-II season of 2012, the mutants BP2/75/2, BP2/75/5 and BP2/100/2 produced significantly higher bulb yields atIshurdi and Magura than the check variety BARI Piaz-3.Unlike Kharif-I season the shelf life of the bulbs of mutants and the check variety did not differ significantly in Kharif-II although yield was almost double. Advance yield trial for seed yield potentialsin 2012-13 of five selected mutants showed all the mutant lines produced sufficient seeds from seed in the same season like preliminary yield trial. Seed production of the mutants ranged from 798-1193 kg/ha with the highest being in BP2/75/3 followed by BP2/75/2 while the parent BARI Piaz-2 produced the lowest seed yield of all.